him Ni un Chamo más: How Peruvian Television Channels have been representing the Venezuelan immigration during the last years: How Peruvian Television Channels have been representing the Venezuelan immigration during the last years - Revilla Arizaca, Christian Fidel (2024)
The Venezuelan diaspora has been the most significant immigration crisis in Latin America during the 21st century, with over 7 million people leaving their country. Peru has been the second most popular destination for Venezuelan immigrants, with over 1.5 million people arriving. Different communication media broadly covered the massive influx of newcomers, portraying it as an unusual phenomenon. Thus, this article focuses on the study of 4 Peruvian television channels and how they depict immigrants. However, the sensationalized coverage by these channels paid more attention to negative aspects such as crime, border crises, and the burden of these immigrants on the recipient country. As a result, this mediated coverage has contributed to the local population’s unfavorable reception of Venezuelans.